A study on thermally regenerative electrochemical cycles using various supercapacitors. (25th November 2022) - Kim, Jaehoon; Kim, Sung Hoon; Lee, Jongho; Seol, Jae Hun
Highlights: TRECs are implemented using different types of supercapacitors. The TREC efficiencies are analyzed considering the energy losses. The TRECs operate over voltage ranges that minimize the impact of self-discharge. The TREC characteristics of the different supercapacitors are elucidated. Abstract: Efficient energy harvesting systems have been developed to recover the low-grade waste heat that is generated by industries. Although there have been several kinds of research studies on thermally regenerative electrochemical cycles using electrochemical cells, an energy harvesting cycle using a lithium-ion capacitor and pseudocapacitor has not yet been examined. This study was conducted to implement a thermally regenerative electrochemical cycle with three different kinds of commercial supercapacitors: a lithium-ion capacitor, a pseudocapacitor, and an electric double-layer capacitor. The thermally regenerative electrochemical cycle of the supercapacitors was configured within a range of voltage values changed by the temperature in an open circuit. This was achieved by designing a reference voltage, i.e., initial voltage, to minimize the effect of self-discharge. The energy harvesting work was analyzed in detail considering the effect of self-discharge. Under the assumption of heat recuperation efficiency of 100%, the thermally regenerative electrochemical cycle efficiencies of the lithium-ion capacitor, pseudocapacitor, and electric double-layer capacitor were 8.77%, 10.2%, and 10.4%, respectively. The energy loss of the pseudocapacitor, which was 34.1%, was the lowest value among those of all supercapacitors; it was confirmed that this pseudocapacitor energy loss was the result of self-discharge and internal resistance.